Reverse osmosis : - Kucera, Jane (Wiley, 2015)
This new edition of the bestselling Reverse Osmosis is the most comprehensive and up-to-date coverage of the process of reverse osmosis in industrial applications, a technology that is becoming increasingly more important as more and more companies choose to “go green.” This book covers all of the processes and equipment necessary to design, operate, and troubleshoot reverse osmosis systems, from the fundamental principles of reverse osmosis technology and membranes to the much more advanced engineering principles necessary for designing a reverse osmosis system.